916 Evaluation of a multidisciplinary cancer clinic: improving time to oncology assessment and treatment for patients with new lung cancer. (21st November 2017) - Stone, Christopher; Brown, Erin; Mates, Mihaela; Falkson, Conrad; Owen, Timothy; Ashworth, Allison; Mahmud, Aamer; Parker, Christopher; Robinson, Andrew; Digby, Genevieve
Abstract : Background: Delays in the management of lung cancer (LC) are associated with inferior outcomes. Multidisciplinary cancer clinics (MDCC) can improve timeliness and quality of care. Objectives: Decrease time from LC diagnosis to oncology assessment from 13 to 3 days, and to treatment from 30 to <20 days, within 6 months. Methods: We implemented a weekly MDCC, involving Respirologists, Medical Oncologists (MO) and Radiation Oncologists (RO), where patients with new LC diagnoses received concurrent oncology consultation. We retrospectively analysed data pre-MDCC (November 2016 – February 2017) and prospectively for improvements (February – July 2017). Improvement cycles included MDCC clinic launching and a debriefing/troubleshooting meeting. Data are reported as n(%), and means as per Statistical Process Control XmR(i) charts. Results: 117 patients (44 pre-MDCC, 73 post-MDCC) were analysed. Most patients had stage 4 (44, 37.6%) or stage 1 LC (32, 27%). All patients saw Respirology, in addition to MO (85, 72.6%), RO (113, 96.6%), or both (83, 71.0%). The proportion of treated patients was unchanged pre- vs. post-MDCC (88.6%, 85.4%). Mean days from diagnosis to oncology assessment decreased from 14.3 to 5.0 days. Time from diagnosis to first treatment decreased from 39.8 to 27.2 days after the first improvement cycle, and to 18.1 days after the second improvement cycle (Figure 1), with less variation in time to treatment after improvement events. Conclusions: MDCC shortens time from LC diagnosis to oncology assessment and treatment. Time to treatment improved more than time to oncology assessment, suggesting the improvement is likely related to benefits beyond just faster oncology assessment.